Effect of thermal radiation on unsteady stagnation-point flow with mass transfer - Md Ali, Fadzilah; Mohd Nazar, Roslinda; Md. Arifin, Norihan (AIP Publishing LLC, 2012)
In this paper, the effect of thermal radiation on unsteady stagnation-point flow of an incompressible viscous fluid with mass transfer is studied. The governing system of partial differential equations is first transformed into a system of ordinary differential equations by a similarity transformation and is then solved numerically by the shooting method. It is found that the surface heat transfer rate reduces when the thermal radiation is applied and dual solutions exist only for negative unsteadiness parameter while positive unsteadiness parameter produces a unique solution.